PENERAPAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IV SD NEGERI 6 SEPOTONG KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Suyetno, Suyetno; Antosa, Zariul; Lazim. N, Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted by the low learning outcomes PKn fourth grade students of SD Negeri 6 Sepotong state Siak Kecil District of Bengkalis, the number of students 20 people. Known to the acquisition of the average value of grade 61 with the medium category and value completeness Individuals declared complete when reaching a value of 65. While the value specified classical completeness is 75. From the average value of 61, only 7 students who completed at a percentage of 25.5%. While students who did not complete 13 people with a percentage of 35.5%. This research is a classroom action research (PTK) using phase 2 cycles. Conducted with the aim to enhance the student's learning outcomes PKn Class IV SDN 6 Sepotong Siak Kecil District of Bengkalis with Application of Contextual Approach. Collecting data in this research is the teacher and student activity sheets and student learning outcomes. In the thesis there is a learning outcome data before an act is done is by the average value of grade 61, increases the action sikus I that the average value of 75.5, and increased again in the second cycle is 78.25. The activities of teachers in the first cycle of meetings I gained an average score of 61.90% with sufficient category. The activities of teachers in the first cycle II meeting to obtain an average score of 66.66% with sufficient category. Furthermore, the activity of the first meeting of the second cycle teachers has increased with the acquisition of an average score of 71.42% with the good category, and the activity of teachers in the second cycle II meeting to obtain an average score of 85.71% with the good category. Activity of students in the first cycle of meetings I gained an average score of 66.66% with sufficient category. Furthermore, increased activity of students in the first cycle II meeting to obtain an average score of 76.19% with the good category. Activity of students in the second cycle meetings I gained an average score of 80.95% with the good category, and increased again in the second cycle II meeting to obtain an average score of 85.71% with the good category. Results of research conducted in class IV SDN 6 Sepotong Siak Kecil District of Bengkalis prove that the Application of Contextual Approach can improve learning outcomes PKn fourth grade students of SD Negeri 6 Sepotong Siak Kecil District of Bengkalis.Keywords :Contextual Approach, To improve Learning outcome PKn